(untitled) (Scientific journal of the Fergana State University, 2024)
The article explains that the main essence of the territorial organization of society is the territorial organization of the population, and the point is that these two concepts cannot be understood separately from each other. One thinks about the extent to which the sciences that study population influence the content of the concept of territorial organization of the population, and in any case, the organization acquires territoriality. Also in the article, territoriality is interpreted as the main criterion for the size of the population and settlements included in the geographical space, and its manifestation through territorial stratification is justified.